Humanos ou cobaias? Trajetórias de cuidado e o desafio do direito à saúde de pessoas travestis e transexuais. - Antognetti, Marcia Regiane Borges [UNIFESP] (2019)
This research aimed to understand the main difficulties and advances to ensure access to health in the context of Public Health Policy, from the perspective of transvestites and transsexuals that use the Health Clinic for transvestites and transsexuals of the Guilherme Álvaro Hospital, in the city of Santos - SP. We mapped the demand for the transsexualization process, as well as the socioeconomic and cultural conditions of this population. The issue of prejudgment, discrimination and violence suffered by transsexuals in their daily lives was addressed, especially with regard to assistance and shelter in the health service. These are people who express themselves in the world according to the gender which they identify themselves, regardless of the biological sex they were born with, making them targets of violence of all kinds and vexatious situations, because they are in disagreement with the cisheteronormative standards that govern our society. Initially, a systematic literature review was conducted as a methodological effort in order to identify the themes that have been explored in the tradition of health itself. We determined for a qualitative research, under the reference of critical and narrative hermeneutics, through the reconstruction of care trajectories. In this study, we detected that from the point of view of transsexuals’ people, the existence of the specific outpatient clinic sounds like an important social gain, coming from the movements between the interested population and the Sexual Diversity Commission of Santos. For being exclusively linked to SUS, even not have their own funds to pay for doctor’s visits, exams and treatments, it is possible to remain in the service, making it an important protagonist in terms of guaranteeing health as a right for all. We identified as the main advances in access to health, the assistance provided by professionals who work directly in the specific outpatient clinic, providing the acquisition of reports for the rectification of the first name and sex judicial process, acquisition of hormones and performance of surgeries, except for sexual reassignment. We attested that transsexuals’ people see transphobia, prejudgment, discrimination, violence and the nonuse of the social name as important factors that prevent them from accessing health, or even associating to it. They are treated with indifference and are often not even listened. They feel as if they were guinea pigs, due to lack of technical ignorance and practical knowledge of the professionals when they are approach with this theme. Interviewees emphasize that, the biggest barrier is the (de)user embracement and (de)assistance. We verified that the guarantee of the right to health depends on the relationships between health professionals and transsexuals’ people, through the recognition of this population and its singularities, as well as the implementation and strengthening of the LGBT public health policy. We have the challenge to ensure the rights to health of this population, injecting ways to raise awareness and qualify professionals, overcoming the barriers mentioned in this study, investing in a humanized user embracement, free of discrimination, prejudgment and violence, in order to flow the happiness projects of each person assisted.